Antibiotic resistance patterns of bacterial strains isolated from Periplaneta americana and Musca domestica in Tangier, Morocco - Lamiaa Bouamamaa; Antonio Sorlozano; Amin Laglaoui; Mariam Lebbadi; Ahmed Aarab; José Gutierrez (Journal of Infection in Developing Countries)
Background:  Flies and cockroaches are two insects in close contact with human beings. They are carriers of human pathogenic bacteria on the external areas of their bodies or in their digestive tracts. This study examines Periplaneta americana and Musca domestica collected from the residential areas of six districts in Tangier, Morocco.